2014
DOI: 10.9753/icce.v34.currents.34
|View full text |Cite
|
Sign up to set email alerts
|

Swash Zone Based Reflection During Energetic Wave Conditions at a Dissipative Beach: Toward a Wave-by-Wave Approach

Abstract: This paper presents a 11-day experiment conducted at the high-energy dissipative beach of Mataquito, Maule Region, Chile. During the experiment, offshore significant wave height ranged 1-4 m, with persistent long period up to 18 s and oblique incidence. Wave energy reflection value ranged from 1 to 4 %, and results show that it is highly linked to both incoming wave characteristics and swash zone beach slope, and is well correlated to a swash-slope based Iribarren number. The swash acting as a low-pass filter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Holman and Sallenger, 1985;Hughes and Moseley, 2007) and interpretation of video records (see Holman and Sallenger, 1985; 20 Ruessink et al, 1998;Stockdon et al, 2006, among many others). More recently, lidar has been used for runup measurement in the field (Blenkinsopp et al, 2010;Almeida et al, 2013;Almar et al, 2014;Fiedler et al, 2015) and for measuring free surface elevations in certain largescale experimental facilities (Blenkinsopp et al, 2012). A review of swash zone hydrodynamics, including the effects on beach morphodynamics, is provided by Brocchini and Baldock (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Holman and Sallenger, 1985;Hughes and Moseley, 2007) and interpretation of video records (see Holman and Sallenger, 1985; 20 Ruessink et al, 1998;Stockdon et al, 2006, among many others). More recently, lidar has been used for runup measurement in the field (Blenkinsopp et al, 2010;Almeida et al, 2013;Almar et al, 2014;Fiedler et al, 2015) and for measuring free surface elevations in certain largescale experimental facilities (Blenkinsopp et al, 2012). A review of swash zone hydrodynamics, including the effects on beach morphodynamics, is provided by Brocchini and Baldock (2008).…”
Section: Introductionmentioning
confidence: 99%
“…The data used in this paper were collected during three experiments undertaken in 2012-2013 at contrasting field sites (Figure 1). A dissipative beach experiment was conducted at Mataquito, Chile, from November 28th to December 14th, 2012 (Figure 1.a, Cienfuegos et al, 2014;Almar et al, 2014a). Mataquito is a medium grain-sized (D50 = 0.2 mm), alongshore uniform, barred beach with a micro-tidal range and a wave climate dominated by swell waves (annual mean significant wave height, Hs ∼ 2.4 m, peak period Tp ∼ 12 s, predominantly from the SW direction).…”
Section: Field Datamentioning
confidence: 99%
“…Despite this, recent observations have shown that saturation can extend to the infragravity band (Ruggiero and Holman, 2004;Senechal et al, 2011) and infragravity waves can be dissipated through breaking (Van Dongeren et al, 2007;de Bakker et al, 2014;Bertin et al, 2018). Observations at very steep beaches show reflection even in the gravity band (Almar et al, 2014;2018a). In the swash zone, several authors (Huntley et al, 1977;Guza and Thornton, 1982;Ruessink et al, 1998) describe a swash spectra saturation roll-off around f 3 (with f the frequency) based on theoretical analysis and observation.…”
mentioning
confidence: 99%